STUDENTS’ MOTIVATION IN WRITING AT LESSON STUDY - Putri, Maya Mutiara; Kayyis, Rahmatika; Kurniati, Kurniati; Wulandari, Fitri; Sugesti, Renita (Jurnal Smart, 2020)
This research was a collaborative action research that was aimed to increase the students’ motivation in writing by Lesson Study at VIII B Ikhwan of SMP IT Insan Mulia Pringsewu, Lampung. There were two cycles in this study. The result of this research presented that Lesson Study gave impact in increasing the students’ motivation; the intrinsic and extrinsic motivation. These aspects influenced and supported each other. After the implementation amount of the students who had good willingness in learning increased becoming more than part of them. Lesson study gave the good impact for both the students and the model teacher.